Prion-like α-synuclein pathology in the brain of infants with Krabbe disease - Hatton, C; Ghanem, SS; Koss, DJ; Abdi, IY; Gibbons, E; Guerreiro, R; Bras, J; Walker, L; Gelpi, E; Heywood, W; Outeiro, TF; Attems, J; et al. (Oxford University Press, 2022)
Krabbe disease is an infantile neurodegenerative disorder resulting from pathogenic variants in the GALC gene that causes accumulation of the toxic sphingolipid psychosine. GALC variants are also associated with Lewy body diseases, an umbrella term for age-associated neurodegenerative diseases in which the protein α-synuclein aggregates into Lewy bodies. To explore whether α-synuclein in Krabbe disease has pathological similarities to that in Lewy body disease, we performed an observational post-mortem study of Krabbe disease brain tissue (n = 4) compared to infant controls (n = 4) and identified widespread accumulations of α-synuclein. To determine whether α-synuclein in Krabbe disease brain displayed disease-associated pathogenic properties we evaluated its seeding capacity using the real-time quaking-induced conversion assay in two cases for which frozen tissue was available and strikingly identified aggregation into fibrils similar to those observed in Lewy body disease, confirming the prion-like capacity of Krabbe disease-derived α-synuclein. These observations constitute the first report of prion-like α-synuclein in the brain tissue of infants and challenge the putative view that α-synuclein pathology is merely an age-associated phenomenon, instead suggesting it results from alterations to biological pathways, such as sphingolipid metabolism. Our findings have important implications for understanding the mechanisms underlying Lewy body formation in Lewy body disease.